Mathematical models to assessment the energy performance of textured cladding for facades - Alchapar Noelia (Tamkang University Press, 2021)
The temperature increase of a city in relation to its peripheral areas leads to the formation of an Urban Heat Island. Working on the Opto-thermal properties of the building envelope is a viable mitigation strategy to reduce the temperatures of a city. Having quantitative data on energy performance allows the development of precise evaluations and the selection of the most efficient data in relation to energy consumption. The degree of efficiency of a material is calculated with an indicator called Solar Reflectance Index (SRI). Since opto-thermal properties change over time, the standard recommends obtaining the SRI level of both new and three-year-aged material (SRI3). In the present work, 80 facade claddings were evaluated to (a) determine which qualitative variables significantly influence the SRI3 of the claddings; (b) obtain an equation that calculates the SRI3 without the need to monitor the large number of variables used for its calculation. For this, the following statistical methods were used: multifactorial ANOVA and linear regression model. In this correlational analysis, color, composition, and texture were selected as independent variables. The research showed that color is the variable that significantly influences SRI3 in all the evaluated claddings. By means of the equation obtained with the regression model, the SRI3 index was predicted to reach 95% IC. These results significantly save time and simplify the process of obtaining data since it is not necessary to monitor numerous input variables to calculate the indicator.